Implementation of CSR Communication in the Textile Industry in Solo Raya - Rahmanto, Andre Noevi; Faridl Widhagdha, Miftah; Priliantini, Anjang; Anshori, Mahfud; Hendriyani, Christina Tri (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
Community service with the topic Implementation of CSR Communication in the Textile Industry for members of the Indonesian Textile Association (API) throughout Central Java aims to enable textile industry players to understand the importance of implementing Corporate Social Responsibility or CSR in maintaining environmental sustainability and empowering communities around factories. In addition, this activity also explained about the company's PROPER assessment, the laws that regulate and influence companies engaged in the textile industry, to the procedures and methods of CSR communication to stakeholders and the involved community. The scope of this community service activity is CSR training, especially in the textile industry. The method is carried out through 4 stages, namely, tests, presentation of material, and discussions and questions and answers. The fact found by the field is that the textile industry business actors do not understand and carry out CSR and their communication methods are right on target. The final result of the activity obtained is that the participants get an overview of good CSR programs and CSR programs that have succeeded in getting the Blue PROPER. This can be seen through the increase in the post test scores compared to the pre test scores at the beginning of the training activities.